APPLICATION OF LINEAR REGRESSION MODELS TO DETERMINE THE EFFECT OF AGE ON MEASURED ANATOMICAL DISTANCES IN THE TREATMENT OF MANDIBULAR FRACTURES IN CHILDREN - Kovach, I.V.; Zub, H.E.; Lokes, K.P. (World of Medicine and Biology, 2024)
The study was devoted to the application of linear regression models to determine the effect of age on measured anatomical distances in the treatment of mandibular fractures in children. The study involved 100 cone-beam computed tomography scans of the skull of children aged 6 to 17 years, which were performed due to traumatic injuries, inflammatory diseases, or jaw tumors. Measurements were taken to identify zones on the mandible for screw fixation during open reduction and internal fixation using mini-plates, aiming to prevent trauma to developing tooth buds, roots of permanent teeth, and the mandibular canal. The results indicated that age influences anatomical distances critical for surgical intervention, necessitating age-specific approaches to minimize the risk of complications during the treatment of mandibular fractures in children.